The Effect of the Crack-Stiffness Relationship on the System Response in Columns of an SDOF Steel Structure Model under Harmonic and Earthquake Excitations - Huseyin Aggumus; Mahmut Daskin; Mehmet Haskul; Abdullah Turan (Shock and Vibration)
In this study, the effects of cracks in the columns of a single degree of freedom (SDOF) steel structure model on the system responses due to the decrease in the equivalent spring coefficient were investigated. The crack in the columns was modeled as an edge crack, and the crack was thought to behave like a spring. The crack is considered as the mode I crack type (opening mode) specified in linear fracture mechanics. In order to examine the responses of the system under the influence of different excitations, the changes in displacement, acceleration, and power spectral density responses under the influence of harmonic excitation at a frequency equal to the fundamental frequency of the SDOF model and six different earthquake excitations were examined.